Circulating cell-free DNA as a biomarker in the diagnosis and prognosis of colorectal cancer - Isadora Bernardo David de Oliveira; Rosario Dominguez Crespo Hirata (Universidade de São Paulo, 2018)
Abstract Colorectal cancer (CRC) is a disease without evident clinical symptoms in early stages, leading to late diagnosis and disease management. Current diagnostic and prognostic tools require invasive procedures and circulating molecular biomarkers fail to have optimal sensitivity and specificity. Circulating biomarkers with high clinical performance may be valuable for early diagnosis and prognosis of CRC. The purpose of this review was to investigate the application of circulating cell-free DNA (ccfDNA) in CRC diagnosis and prognosis and the analytical methods used in blood samples in articles published between 2005 and 2016. Based on specific inclusion and exclusion criteria, 26 articles were selected. Most studies used ccfDNA quantification as the molecular biomarker. The analytical method was mainly based on the quantitative polymerase chain reaction (qPCR). Biomarkers based on aberrantly methylated genes (n=6) and ccfDNA integrity/fragmentation (n=2) were also used for the CRC diagnosis. The CRC prognosis used the detection of oncogene mutations, such as KRAS and BRAF, in ccfDNA. Significant differences were found in variables among the studies revealing potential bias. ccfDNA quantification as a diagnostic biomarker for CRC has promising results but it lacks clinical specificity since other diseases present a similar increase in ccfDNA content. However, increasing research in the epigenomic field can lead the way to a clinically specific biomarker for the CRC early diagnosis. As for the analytical method, qPCR and derivatives seem to be a perfectly valid technique. The use of ccfDNA quantification in CRC prognosis seems promising. The attempt to use the ccfDNA quantification in clinical practice may reside in the prognosis using a qPCR technique.